FAŁSZOWANIE OZNACZEŃ AUTORSTWA W STAROŻYTNYM RZYMIE A USTAWA ‘LEX CORNELIADE FALSIS’ - Kręźlewicz, Katarzyna (Zeszyty Prawnicze, 2016)
FALSE DESIGNATION OF AUTHORSHIP IN ANCIENT ROME AND THE LEX CORNELIA DE FALSIs Summary The lex Cornelia testamentaria nummaria, later known as the lex Cornelia de falsis, was the first Roman comprehensive anti-fraud law. Initially its scope only covered forged wills and counterfeit coinage. In the early first century AD other documents were given legal protection under criminal law against forgery. Later Roman anti-fraud laws were expanded to cover cases of falsifying documents, making false statements, corrupting judges, and adulterating and using adulterated weights and measures. There was no legal definition in ancient Rome of the trademark in the modern sense, but craftsmen’s stamps and workshop marks, which had been in use since time immemorial and were an indispensable appurtenance associated with the expansion of the Roman Empire and the growth of its trade, played a similar role. The use of false or forged designations could presumably be treated as analogous to the use of a false identity, which was punishable by the poena legis Corneliae. However, there are no Roman law sources showing evidence of protection for this kind of designation. Presumably there was a need for craftsmen’s marks to inform buyers about a product’s origin and features. Yet the real purpose of those descriptions was to protect the interests of the craftsman or producer, while the protection of his customers was more of an indirect effect. There are no sources to unequivocally confirm the punishability of counterfeiting craftsmen’s marks and the treatment of the phenomenon as fraud. The Roman legislator did not perceive the use of forged designations as a violation of the public good, but rather only as a risk which individual craftsmen or producers had to reckon with. The lex Cornelia penalised conduct that could affect the interest of the public and state. In the opinion of the Roman legislator false authorship only violated the interest of the producer concerned.